Studi Naratif Syeikh Azra’i Abdurrauf Tentang Pembentukan Akhlaqul Karimah Melalui Seni Baca Al-Qur’an - Muhammad, Irsyad; Andy, Safri (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2023)
Shaykh Azra'i Abdurrauf is a scholar who contributes to the world of reading the Al-Quran by wholeheartedly practicing and teaching adab and learning to read the Al-Quran in the field of interpretation, the tafsir of tajwid, makhraj science and adab in the art of reading the Al-Quran. This study aims to emulate Shaykh Azra'i Abdurrauf in the formation of Akhlakul Karimah through the art of reading the Al-Quran. This study uses qualitative methods with a narrative study approach to describe events in detail and related. The stages of data processing are carried out, namely data collection, data reduction and drawing conclusions. The results of the study show the contribution of Shaykh Azra'i Abdurrauf in implementing, teaching the values of Akhalqul Karimah to Muqri, students and Muslims.